LuAG:Pr codoped with Ho3+: Acceleration of Pr3+ decay by energy transfer. (May 2019) - Páterek, Juraj; Král, Robert; Pejchal, Jan; Prokeš, Radek; Nikl, Martin
Abstract: Ho 3+ codoping of Lu3 Al5 O12 activated with Pr 3+ (LuAG:Pr) induces an acceleration of Pr 3+ decay kinetics. This is caused by nonradiative energy transfer from Pr 3+ to Ho 3+ driven by a multipolar electromagnetic interaction. Luminescence and scintillation properties of LuAG:Pr codoped with Ho 3+ ions were studied over a wide concentration range. A significant acceleration of response was achieved. The Förster-Dexter model was used to analyze the decay kinetics of the Pr 3+ luminescence center and the interaction between Pr 3+ and Ho 3+ ions. Several concentration characteristics useful for tailoring the timing and light output properties are presented. Highlights: The effect of Ho 3+ codoping of LuAG:Pr is studied over a wide range of Ho 3+ concentrations. The inherent decay time of Pr 3+ in LuAG host is shortened by Ho 3+ codoping. The scintillation response of LuAG:Pr is accelerated by Ho 3+ codoping. Useful concentration dependences of timing and light output properties are obtained.